ESTIMASI KANDUNGAN CARBON NEKROMASA DI HUTAN LARANGAN ADAT KENAGARIAN RUMBIO KECAMATAN KAMPAR SEBAGAI RANCANGAN MODUL PADA PEMBELAJARAN BIOLOGI SMA - Irfan Irfan; Sri Wulandari; Yuslim Fauziah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The study aims to see the carbon potential stored in tree and litters atHutan Larangan Adat Kenagarian Rumbio Kampar District and its potential to producedesigns of air pollution modules in tenth grade high school biology study. The study wasconducted from January to February 2019. This research was a descriptive study usingsurvey methods in Hutan Larangan Adat Kenagarian Rumbio and in Biology educationnatural laboratory Faculty of Teacher Training and Education University of Riau. Theslection of location was purposive sampling, which there are 3 stations based on threevegetative conditions that are dense, average and distantly, on each transet or stationusing 10 main 20x20 meter length for tree measurements and subplots 1x1 meter lengthfor litters measurements. The results showed potential of nechromass carbon in HutanLarangan Adat Kenagarian Rumbio at 8,27 ton/ha for tree nechromass and 4,48 ton/hafor litters nechromass,the study also has the potential to be a design module for airpollution materials in 10th grade high school biologi study.Key Words: Nechromass, carbon, Air pollution